Estudo comparativo da resposta inflamatória de vias aéreas em corredores de rua e sedentários expostos a diferentes níveis de poluição atmosférica - Sá, Matheus Cavalcante de [UNIFESP] (2018)
There are several deleterious effects on human health caused by air pollution in the upper airways tract (UAT) of the population living in large cities. The present study sought to compare the effects of air pollution on the UAT of runners and sedentary people, residents of the metropolitan region of São Paulo. Fiftyfour volunteers were followed up for a year and collected the biological materials and the characterization tests of the samples were carried out in the following seasons: PreWinter (PW) first day of winter; Winter (W) middle of the winter season; PreSummer (PS) early summer season; and Summer (S) middle of the summer season. The collections took place between June 2016 and February 2017. The levels of ozone (O3), particulate matter (PM10) and fine particulate matter (PM2.5) in the metropolitan region of São Paulo were measured. From each participant the serum vitamin D level, the exhaled nitric oxide fraction (FeNO). the pH of the exhaled air condensate (pH EBC), nasal wash pH (pH LN), ciliary mucosal transport time (TMC), differential cell counts, oxidative stress markers (TAC, Hydrogen Peroxide and Nitric Oxide) of EBC and LN, as well as the IL1ra, IL10 and TNFα cytokines of the LN. A significant difference of PM10 and PM2.5 was observed between collection seasons. Runners had better levels of Vitamin D in the summer and a drop in the local inflammatory marker (IL1ra of the LN) in both groups (runners and sedentary) in winter analyzes and a significant increase in IL10 production (marker antionly in the group of runners in the summer. TMC showed a significant increase in sedentary individuals in prewinter collections. The results obtained so far in this research provide support for the assertion that regular physical exercise, exposed to the same air pollution conditions as sedentary ones during the whole cycle of seasons, develop ways to block the deleterious effect of air pollution through the mechanism of inflammation and control of inflammation of the UAT.